Women of the Jungle: Guerrilleras on the front lines of the FARC-EP - Welsh, Alexandra Mary (Glendon Journal of International Studies, 2015)
The world of South American revolutionary groups is one that is full of imagery of machismo and legends of guerillas. However, women are often heavily represented in their ranks as fighters, or guerrilleras. Such is the case with Fuerzas Armadas Revolucionarios Colombianos – Eje´rcito del Pueblo (FARC-EP), the oldest revolutionary group in Colombia, who report that 20-40% of their members are female. The leadership of the FARC-EP declared in 1985 that women would be considered equal as fighters within their organization. This made their revolutionary group a place of equality in a country where women are offered little agency over their own lives. Along with this parity between the sexes found officially within the movement, taking on the role of a guerrillera also offers women protection from domestic violence and targeted violence waged by other guerilla groups. It also places them in a position of prestige as a combatant and revolutionary. While the lives of these women, spent largely in the jungle, are very difficult, the socio-economic realities of being a rural woman in Colombia make membership in the FARC-EP a viable, and sometimes preferable, alternative. Le monde des groupes révolutionnaires sud-américains est rempli d’images machiste et de légendes de guérillas, toutefois les femmes sont souvent hautement représentées dans leurs rangs de combattantes, ou guerilleras. Le cas notamment des Fuerzas Armadas Revolucionarios Colombianos - Ejército del Pueblo (FARC-EP) représente le plus vieux groupe révolutionnaire de la Colombie et signale que 20 à 40% de leurs membres sont des femmes. La direction du FARC-EP a déclaré en 1985 que les femmes seront considérées égales aux hommes en tant que combattantes au sein de leur organisation, créant ainsi un lieu d'égalité au sein de leur groupe révolutionnaire dans un pays où les femmes normalement possèdent peu de contrôle sur leurs propres vies. Avec la parité des sexes officiellement dans le mouvement, le rôle de guerilleras offre aussi aux femmes une protection contre la violence domestique et la violence ciblée des autres groupes guerillas. Les femmes sont aussi placées dans des positions de prestige comme combattantes et révolutionnaires. La vie de ces femmes se passe largement dans la jungle et est souvent très difficile; les réalités socio-économiques d’une femme rurale colombienne transforment l’adhésion au FARC-EP en alternative viable et parfois même préférable à tout autre mode de vie accessible à celle-ci.